SARS‐CoV‐2 antibody responses in solid organ transplant recipients. Issue 5 (22nd September 2021) - Zervou, Fainareti N.; Ali, Nicole M.; Neumann, Henry J.; Madan, Rebecca Pellett; Mehta, Sapna A.
Abstract: Antibody responses among immunocompromised solid organ transplant recipients (SOT) infected with Severe Acute Respiratory Syndrome Coronavirus‐2 (SARS‐CoV‐2) may be diminished compared to the general population and have not been fully characterized. We conducted a cohort study at our transplant center to investigate the rate of seroconversion for SARS‐CoV‐2 IgG antibodies among SOT recipients who were diagnosed with Coronavirus disease 2019 (COVID‐19) and underwent serum SARS‐CoV‐2 IgG enzyme‐linked immunosorbent assay (ELISA) testing. The 61 patients who were included in the final analysis underwent initial SARS‐CoV‐2 IgG testing at a median of 62 days (Interquartile range 55.0–75.0) from symptom onset. Note that, 51 of 61 patients (83.6%) had positive SARS‐CoV‐2 IgG results, whereas 10 (16.4%) had negative IgG results. Six (60%) out of 10 seronegative patients underwent serial IgG testing and remained seronegative up to 17 weeks post‐diagnosis. Use of belatacept in maintenance immunosuppression was significantly associated with negative IgG antibodies to SARS‐CoV‐2 both in univariate and multivariate analyses (Odds ratio 0.04, p  = .01). In conclusion, the majority of organ transplant recipients with COVID‐19 in our study developed SARS‐CoV‐2 antibodies. Further longitudinal studies of the durability and immunologic role of these IgG responses and the factors associated with lack of seroconversion are needed.